Pengaruh Net Profit Margin dan Total Asset Turnover terhadap Nilai Perusahaan, Dimoderasi oleh Earning Per Share - Natalia Caroline; Santi Dwi Mulyati; Aprildawati Sinaga (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study investigates the effects of Net Profit Margin (NPM) and Total Asset Turnover (TATO) on firm value, with Earnings Per Share (EPS) as a moderating variable, in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Firm value is measured using the Price-to-Book Value (PBV) ratio as a market-based indicator. A quantitative explanatory research design is employed using 120 observations from 24 companies over five years, using panel data regression with Moderated Regression Analysis (MRA) and robust standard errors. The results that NPM has a significant negative effect on PBV, whereas TATO has a significant positive effect. EPS does not have a significant direct effect on PBV, but it moderates the relationship between NPM and firm value. In contrast, EPS does not moderate the effect of TATO on PBV. These findings indicate that, in the transportation sector, investors place greater emphasis on asset utilization efficiency, while profit margins are more highly valued when they translate into higher earnings per share.